Lumbung Desa in Java: A Credit Institution, Poverty Management, and Financial Problem Solving for Villagers During the Colonial Period - Haryono Rinardi; Yety Rochwulaningsih; Titiek Suliyati; Sutejo K. Widodo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
This paper aims to examine the existence and development of Lumbung Desa or village rice barns as a credit institution during the colonial era. It was expected to be an inspiration and reference to revitalize, design, and develop barns at the village level that contributed significantly to the village welfare at the recent time. Therefore, how and why was Lumbung Desa institution able to develop during the colonial era? How much was its contribution to the village welfare? To examine these questions, the authors used critical historical method and through economical and sociological approach. The result shows that Lumbung Desa was formed and developed by the Dutch to overcome poverty as a strategic issue at the time, especially at village level. The grand design program of Lumbung Desa was to channel loan schemes especially and savings that could be in the form of in cash or rice. It was used to help farmers against the middlemen and moneylenders who were considered as adverse parties for the villagers. Lumbung Desa existed and was managed in many villages of Java during the colonial era. It relied on rural communities with distinctive personal socio-economic relations that brought about both strengths and weaknesses for the institution. However, there were some advantages of Lumbung Desa; first, it provided loans in two types, cash and/ or rice which became major and urgent needs for the villagers; second, its presence in rural areas made farmers become customers and easily access the market; third, its flexibility made it easily transform according to rural community needs.